The Development Strategy of Local Shop to Promote the Economic Strength of the Community - Ronnahong-sa, Suwan; Buripakdee, Chaloi; Saengthong, Suchart (Richtmann Publishing, 2013)
This study is a quantitative and qualitative research. The quantitative was quasi-experimental research with one group pretestposttestdesign was used to study and analyze the problem of Houna village’s people. The samples for trial the developmentstrategy of local shop to promote the economic strength of the community were 60 peoples used as the experimental group.The sample groups were selected by purposive selection. Then results were compared between before and after the trial for 6months. The mean differences before and after treatment were analyzed by t-test dependent. The developed strategy wasevaluated by rating scale and the data were analyzed with the mean and standard deviation. The results revealed that themodel of local shop showed that the less income people suffered from lack of source for buying a reasonable prize of good.The suffering of customer from analysis was found target problem that lack of shop selling with reasonable prize. The In-Deptinterview was conducted with experimental group of 60 peoples. It was found that as whole of development strategy, they hadknowledge and understanding of local shop development with 44 percents. Considering to each aspect, it was found thatstrategy for local shop establishment with 47 percents, local shop establishment with 90 percents, local shop membershipsystem with 90 percents, local shop management with 16.38 percents, saving with 53 percents, and community productpromotion with 63 percents. The development strategies were included from the focus group discussion, therefore the workunit systems were as the followings.1) The appropriate local shop model 2) Local shop establishment 3) The trial managementof local shops 4) Evaluation of local shop management and service. The result of trail development strategy was revealed asthe following: 1. Comparison training achievement of participants between before and after, it was found that after training theachievement was higher than before with statistical significance at level of 0.5. 2.Evaluation of the successful results was asthe followings. 2.1 Comparison of opinion of community people before and after experiment, it was found that the communitystrength was more than before with statistical significance at level of 0.5. 2.2 The satisfaction to strategy for development oflocal shop of 60 members had mean at more level (3.80). 2.3 Result of quality evaluation to strategy for development of localshop at the end of the first month and forth month, it was found that the forth month was higher than the first month withstatistical significance at level of 0.5.